High pressure studies on α-cristobalite form of Al0.5Ga0.5PO4: hydrostatic versus non-hydrostatic conditions. Issue 1 (2nd January 2019) - Dwivedi, Abhilash; Poswal, H. K.; Pandey, K. K.; Liermann, H.-P.; Murli, Chitra; Deo, M. N.
ABSTRACT: High pressure angle-dispersive X-ray diffraction investigations have been carried out on α- cristobalite form of Al0.5 Ga0.5 PO4 . Our investigations show that the structural stability of this phase under high pressure depends on the nature of pressure conditions in the diamond anvil cell. Under hydrostatic pressure conditions using neon as a pressure transmitting medium, ambient orthorhombic C2221 phase transforms to orthorhombic Cmcm phase at 4.9 GPa. The high pressure Cmcm phase remains stable up to the highest pressure in the experiment, i.e . 19 GPa. The values of bulk modulus for C2221 and Cmcm phases are 19(2) and 126(4) GPa, respectively. In contrast to this, under non-hydrostatic pressure conditions, transformation of ambient C2221 phase to Cmcm phase has not observed up to 17.4 GPa. Instead, a new monoclinic phase P21 is observed which contains layers of six coordinated Al/Ga ions separated by less dense five coordinated Al/Ga ions.